Efektivitas LKPD Elektronik dengan Problem Based Learning (PBL) dalam Meningkatkan Minat Belajar Siswa - Sari, Eka Mustika; Yulianti, Evy (Postgraduate, University of Mataram, 2025)
Increasing students' interest in learning is a key factor in achieving effective and optimal educational outcomes. One approach that can enhance students' learning interest is through the use of electronic student worksheets, which encourages students to actively engage in the learning process. This study aims to evaluate the effectiveness of electronic student worksheet based on Problem Based Learning (PBL) to enhancing students' learning interests. This research uses a one-group pretest-posttest design involving 27 students from the XI MIPA class at SMAN 1 Jetis, selected through random sampling. IBM SPSS 25 was used to analyze the data using the Wilcoxon test and N-gain. Following the intervention, students' interest in learning increased significantly, according to the study's findings, with an average pretest score of 48.11 and a posttest score of 64.15. The results of the Wilcoxon test indicated a significant difference between the pretest and posttest scores, with a significant value of 0.000 (p < 0.05). In addition, the N-gain results show an average percentage increase of 56.46%, which falls into the quite effective category.